1998
DOI: 10.1046/j.1365-313x.1998.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards functional characterisation of the members of theR2R3‐MYBgene family fromArabidopsis thaliana

Abstract: SummaryTranscription factors containing a conserved DNA-binding domain similar to that of the proto-oncogene c-myb have been identified in nearly all eukaryotes. MYB-related proteins from plants generally contain two related helix-turnhelix motifs, the R2 and R3 repeats. It was estimated that Arabidopsis thaliana contains more than 100 R2R3-MYB genes. The few cases where functional data are available suggest an important role of these genes in the regulation of secondary metabolism, the control of cell shape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
536
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 547 publications
(572 citation statements)
references
References 40 publications
21
536
1
3
Order By: Relevance
“…The first MYB gene identified in plants was C1 from maize, which is involved in anthocyanin biosynthesis [1]. Since then, several MYB genes have been isolated [2][3][4][5]. Recently, Chen et al [6] found 198 MYB genes from Arabidopsis and 183 from rice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first MYB gene identified in plants was C1 from maize, which is involved in anthocyanin biosynthesis [1]. Since then, several MYB genes have been isolated [2][3][4][5]. Recently, Chen et al [6] found 198 MYB genes from Arabidopsis and 183 from rice.…”
Section: Introductionmentioning
confidence: 99%
“…MYB proteins play important roles in multiple aspects of plant growth and development [2][3][4][5]. Several MYB proteins may be involved in secondary metabolism [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The AtMYB44 gene is upregulated by a variety of hormone treatments, abiotic stresses and microbial infections (Jung et al, 2010;Kranz et al, 1998;Yanhui et al, 2006). AtMYB44 regulates diverse cellular responses mediated by abscisic acid (Jung et al, 2008), jasmonate (Jung et al, 2010) and ethylene (Liu et al, 2010;Lü et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among 198 genes in the MYB superfamily, a total of 126 R2R3 MYB-encoding genes have been identified in the Arabidopsis genome, making it one of the largest transcription factor groups in this plant (Yanhui et al, 2006). Extensive functional analyses using large-scale insertional mutagenesis (Meissner et al, 1999;Stracke et al, 2001) and expression profiling (Kranz et al, 1998;Yanhui et al, 2006) have been performed to characterize R2R3 MYB proteins in Arabidopsis. In parallel, the roles of individual R2R3 MYB proteins in diverse plant processes have been explored, including hormonal signaling, cellcycle control, stress responses, secondary metabolism, cellular morphogenesis and meristem formation (Das et al, 2012;Jin and Martin, 1999;Martin and Paz-Ares, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation